2018
DOI: 10.3390/ijms19061593
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiles of SmWRKY Family Genes and Their Putative Roles in the Biosynthesis of Tanshinone and Phenolic Acids in Salvia miltiorrhiza

Abstract: Salvia miltiorrhiza Bunge is a Chinese traditional herb for treating cardiovascular and cerebrovascular diseases, and tanshinones and phenolic acids are the dominated medicinal and secondary metabolism constituents of this plant. WRKY transcription factors (TFs) can function as regulators of secondary metabolites biosynthesis in many plants. However, studies on the WRKY that regulate tanshinones and phenolics biosynthesis are limited. In this study, 69 SmWRKYs were identified in the transcriptome database of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 60 publications
(68 reference statements)
1
34
0
Order By: Relevance
“…The genome sequence and transcriptome analysis of Danshen from various development periods [79], different tissues [10], and tissue cultures from different induction times were taken [11], which provide a foundation for the biological analysis of this useful medicinal plant. Based on these analyses, the biosynthesis and regulation of tanshinones and phenolic acids have made great strides [1214]. However, there are still many aspects that need to be studied based on comparative omics data and genome sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…The genome sequence and transcriptome analysis of Danshen from various development periods [79], different tissues [10], and tissue cultures from different induction times were taken [11], which provide a foundation for the biological analysis of this useful medicinal plant. Based on these analyses, the biosynthesis and regulation of tanshinones and phenolic acids have made great strides [1214]. However, there are still many aspects that need to be studied based on comparative omics data and genome sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors (TFs) comprise diverse gene families that play key regulatory roles in plant growth and development by controlling the expression of genes through specific binding to cis -regulatory elements that are present in the promoter regions of target genes. Many TF families are known to regulate secondary metabolite biosynthesis in plants including the MYB, MYB-related, WRKY, and bHLH families ( Park et al., 2008 ; Hichri et al., 2010 ; Xie et al., 2016 ; Yin et al., 2017 ; Yu et al., 2018 ). Our analysis of the L. longituba transcriptome data revealed that 38347 unigenes (11.50%) encode putative TFs that can be classified into 58 TF families ( Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hairy roots are plant roots genetically transformed with the help of Agrobacterium rhizogenes that exhibit neoplastic growth and can be maintained indefinitely in sterile media without externally added phytohormones [12,13]. Because hairy root cultures consist entirely of differentiated roots and can be easily cloned, they are an ideal model for studies of root biochemistry [14,15] and root-specific processes such as nodulation [16] and the synthesis of root-specific metabolites [17]. Hairy roots also proved useful in studies of interactions between crop plants and herbivores [18].…”
Section: Introductionmentioning
confidence: 99%